Habitual sleep patterns of junior elite athletes in cross-country skiing and biathlon: A descriptive study - Hrozanova, M.; Moen, F.; Myhre, K.; Klöckner, C.; Pallesen, S. (Cogent Medicine, 2018)
Sleep is an essential part of athletes` recovery process. Evidence of the habitual sleep patterns among junior elite athletes is however limited. Most previous sleep studies on this population have typically spanned short periods and employed instruments with restricted validity. Overcoming these limitations, the current study investigated the habitual sleep patterns of 31 junior elite athletes over up to four consecutive months, using a non-invasive radio ultra-wideband radar technology for sleep monitoring. The athletes obtained 07:21 ± 1:21 h of sleep per night, with an average sleep efficiency of 89.5 ± 5.5%. Sleep patterns were affected by weekends and the competitive season. Longer total sleep time, later sleep onset and later sleep offset characterized the weekends, while longer total sleep time and earlier sleep onset were registered during the competitive season. Further, changes in sleep onset and sleep offset carried over to the subsequent day (i.e. the value of these variables at one night depended on the values of the same variable on the night before). It is concluded that junior elite athletes do not adhere to regular sleep-wake patterns, which may lead to various negative consequences. The current study provides novel normative data of junior elite athletes' habitual sleep patterns spanning up to four months, with evidence of large variabilities in the measured sleep parameters, including effects of weekends and competition season.